2016
DOI: 10.1139/cjce-2015-0241
|View full text |Cite
|
Sign up to set email alerts
|

Stream habitat connectivity in the Canadian Arctic: an on-site approach to design and construction

Abstract: We developed a successful on-site approach for design and construction of stream modifications that addressed challenging remote-site conditions of limited field data and available construction materials. Fish habitat connectivity enhancements were constructed within an Arctic headwater stream containing a naturally impassable cascade section with 13% slope, which was bypassed in a newly constructed channel at 5% slope with nature-like fishpass structures. Primary design considerations included (1) creating su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Grayling in low-gradient Barrenlands streams (see also Courtice et al 2014). Furthermore, for these larger Arctic Grayling (≥150 mm), the probability of a passage event through the M2S nature-like fishpass was not related to fish FL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grayling in low-gradient Barrenlands streams (see also Courtice et al 2014). Furthermore, for these larger Arctic Grayling (≥150 mm), the probability of a passage event through the M2S nature-like fishpass was not related to fish FL.…”
Section: Discussionmentioning
confidence: 99%
“…at northern latitudes, rapid increases in discharge and stream velocity during freshets have frequently been cited as critical cues for spring movements (Gustafson 1949;Witkowski and Kowalewski 1988;Northcote 1995;Jones et al 2003a). Indeed, Arctic Grayling often spawn in small streams during freshets (Northcote 1995;Stewart et al 2007), the onset of which is rapid, variable in timing among years, and of short duration (i.e., 5-10 d; Jones et al 2003a;Courtice et al 2014). Moreover, field observations suggested that Arctic Grayling appear in streams and fishpasses almost immediately after the freshet begins (Cahill et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation